Recasting inequality: residential segregation by caste over time in urban India. (October 2019) - Singh, Gayatri; Vithayathil, Trina; Pradhan, Kanhu Charan
This paper analyses residential segregation over time in Indian cities. We examine the change in caste-based segregation longitudinally, while exploring how caste dynamics manifest differently across city size and region. The paper uses successive rounds of decennial census data, from 2001 and 2011. Contrary to expectations, we find residential segregation by caste/tribe persisting or worsening in 60 per cent of cities in our all-India sample, with differences by region and city size. For example, in the states of Karnataka, Haryana, Punjab and Tamil Nadu, a majority of cities experienced decreasing levels of residential segregation by caste/tribe, while in Maharashtra and Gujarat, 34 and 29 per cent of cities, respectively, experienced an increase. A greater proportion of small cities (population 20, 000–49, 999) than large cities (100, 000–999, 999) experienced an increase in residential segregation between 2001 and 2011. Across all city-size categories, the dominant trend has been no improvement in residential segregation by caste/tribe over time.